Energy transitions in Europe - Madureira, N. (Economic history of the European energy industry: Lighting up Western Europe, 19th to 21st centuries, 2024)
This chapter explains the diversity in energy transitions taking place in Europe between the eighteenth and twenty-first centuries. This thus demonstrates how Europe experienced two different transitions from the epoch-long solar energy regime to the coal-based regime. This also points out how the transition towards oil and natural gas differed completely from the previous transition to coal because it was swifter, overwhelming and led by a different group of nations. After the Second World War, the European split between a capitalist West and a communist East also imparted a division between oil and coal economies. What we may expect from the current transition to renewable energy accounts for the chapter’s closing theme.